A multicenter study of acute testicular torsion in the time of COVID-19. Issue 4 (August 2021) - Holzman, Sarah A.; Ahn, Jennifer J.; Baker, Zoe; Chuang, Kai-wen; Copp, Hillary L.; Davidson, Jacob; Davis-Dao, Carol A.; Ewing, Emily; Ko, Joan; Lee, Victoria; Macaraeg, Amanda; Nicassio, Lauren; et al.
Summary: Background: Testicular torsion is a surgical emergency, and time to detorsion is imperative for testicular salvage. During the COVID-19 pandemic, patients may delay emergency care due to stay-at-home orders and concern of COVID-19 exposure. Objective: To assess whether emergency presentation for testicular torsion was delayed during the COVID-19 pandemic, and whether the rate of orchiectomy increased compared to a retrospective period. Study design: Patients were prospectively enrolled in a multicenter study from seven institutions in the United States and Canada. Inclusion criteria were patients two months to 18 years of age with acute testicular torsion from March through July 2020. The retrospective group included patients from January 2019 through February 2020. Statistical analysis was performed using Kruskal–Wallis tests, Chi-square tests, and logistic regression. Results: A total of 221 patients were included: 84 patients in the COVID-19 cohort and 137 in the retrospective cohort. Median times from symptom onset to emergency department presentation during COVID-19 compared to the retrospective period were 17.9 h (IQR 5.5–48.0) and 7.5 h (IQR 4.0–28.0) respectively (p = 0.04). In the COVID-19 cohort, 42% of patients underwent orchiectomy compared to 29% of pre-pandemic controls (p = 0.06). During COVID-19, 46% of patients endorsed delay in presentation compared to 33% in the retrospective group (p = 0.04). Discussion: We found a significantly longer time from testicular torsion symptom onset to presentation during the pandemic and a higher proportion of patients reported delaying care. Strengths of the study include the number of included patients and the multicenter prospective design during the pandemic. Limitations include a retrospective pre-pandemic comparison group. Conclusions: In a large multicenter study we found a significantly longer time from testicular torsion symptom onset to presentation during the pandemic and a significantly higher proportion of patients reported delaying care. Based on the findings of this study, more patient education is needed on the management of testicular torsion during a pandemic.